Makna Harta dalam Akuntansi Syariah Terhadap Budaya Konsumsi Simbolik Generasi Z Muslim Digital - Aulia Ratu Ayu Cahyani; Devina Samantha; Fitrah Riza Pertiwi; Masyhuri Masyhuri (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the meaning of wealth from a sharia accounting perspective on the symbolic consumption culture of Generation Z Muslims in the digital era. The development of information technology and social media has encouraged the emergence of consumption patterns that are not only oriented towards fulfilling needs, but also as a means of building identity, gaining social recognition, and demonstrating status in the digital environment. This phenomenon makes wealth have a broader meaning than its economic function. The study used a descriptive qualitative method with a literature study approach through the review of various scientific sources, sharia accounting concepts, and social phenomena developing in digital media. The results show that the symbolic consumption culture of Generation Z Muslims is influenced by social media exposure, lifestyle trends, and the need for self-existence. From a sharia accounting perspective, wealth is seen as a trust from Allah SWT that must be managed responsibly, balanced, and in accordance with the principles of maqashid sharia. Therefore, a proper understanding of the value and function of wealth in Islam can be a foundation for Generation Z Muslims to form wiser, more proportional consumption behavior, and avoid excessive and consumptive attitudes in the digital era.